2016
DOI: 10.1093/mnrasl/slw224
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for strong evolution in galaxy environmental quenching efficiency between z = 1.6 and z = 0.9

Abstract: We analyse the evolution of environmental quenching efficiency, the fraction of quenched cluster galaxies that would be star-forming if they were in the field, as a function of redshift in 14 spectroscopically confirmed galaxy clusters with 0.87 < z < 1.63 from the Spitzer Adaptation of the Red-Sequence Cluster Survey (SpARCS). The clusters are the richest in the survey at each redshift. Passive fractions rise from 42 +10 −13 % at z ∼ 1.6 to 80 +12 −9 % at z ∼ 1.3 and 88 +4 −3 % at z < 1.1, outpacing the chang… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
113
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(133 citation statements)
references
References 58 publications
16
113
3
1
Order By: Relevance
“…as seen in Figure 7, at least for the clusters shown. This is at odds with the work by Nantais et al (2017), where environmental quenching efficiency was shown to strongly evolve between z = 1.6 and z = 0.9. However, the apparent absence of evolution at high masses that we find would be consistent with the scenario discussed previously, in which the three high-redshift clusters given in Figure 5 were more evolved than the average z 1.6…”
contrasting
confidence: 70%
See 1 more Smart Citation
“…as seen in Figure 7, at least for the clusters shown. This is at odds with the work by Nantais et al (2017), where environmental quenching efficiency was shown to strongly evolve between z = 1.6 and z = 0.9. However, the apparent absence of evolution at high masses that we find would be consistent with the scenario discussed previously, in which the three high-redshift clusters given in Figure 5 were more evolved than the average z 1.6…”
contrasting
confidence: 70%
“…We also calculated the cluster conversion fraction, or efficiency of quenching due to environment, according to the relation f f Phillips et al 2014;Balogh et al 2016;Nantais et al 2017). We give these values in Table 1 to facilitate comparison with other cluster studies, but leave interpretation of our values for future work.…”
Section: The Quiescent Fraction In Irc 0218 and The Fieldmentioning
confidence: 99%
“…Simulations by Muldrew et al (2015) indicate that with increasing redshift, the properties and halo distributions of current epoch massive clusters vary significantly. Variations in quenching efficiencies in cluster environments are found to be largest in higher redshift samples (Nantais et al 2017), suggesting halo mass or age may be dominant factors in galaxy evolution within cluster environments. The halo mass may also directly play a role in the number of mergers seen (Brodwin et al 2013), with more massive clusters assembling mass at earlier epochs whereas proto-clusters of the same epoch will still be assembling and accreting members.…”
Section: Discussionmentioning
confidence: 99%
“…to z 1 (e.g., van der Burg et al 2013;Darvish et al 2016;Nantais et al 2016Nantais et al , 2017) is thus unlikely to be due to enhanced galaxy-galaxy merging, at least in the most massive cluster systems. This suggests that the driving forces in quenching cluster galaxies are more likely to be due to interactions within the intracluster medium (such as ram-pressure stripping), harassment, or mass-induced selfquenching (e.g., Peng et al 2010;Bialas et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Several large projects are exploiting mid-infrared data to search for high-redshift galaxy clusters using Spitzer and WISE (e.g., Eisenhardt et al 2008;Galametz et al 2010Galametz et al , 2013Papovich et al 2010;Stanford et al 2012Stanford et al , 2014Muzzin et al 2013;Rettura et al 2014;Wylezalek et al 2014;Brodwin et al 2015Brodwin et al , 2016PaternoMahler et al 2017). Such work has, for example, proved useful for (i) measuring the galaxy cluster autocorrelation function out to z∼1.5, which provides a measure of the typical galaxy cluster mass (Brodwin et al 2007); (ii) targeted cosmological surveys for z>1 SNe Ia in dust-free environments (Suzuki et al 2012); (iii) probing evolution in the σ-T x correlation (Brodwin et al 2011); (iv) using the rest-frame near-infrared luminosity function and rest-frame optical colors to probe the formation epoch of cluster galaxies (Mancone et al 2010Snyder et al 2012;Wylezalek et al 2014;Cooke et al 2015; Nantais et al 2016); (v) probing the role of AGN feedback in forming clusters (Galametz et al 2009;Martini et al 2013); (vi) leading cosmological investigations based on the incidence of massive, high-redshift clusters Gonzalez et al 2012);and (vii) probing the dependency of galaxy quenching on environment (Muzzin et al 2014, Nantais et al 2017.…”
Section: Introductionmentioning
confidence: 99%